Flavius Josephu s interpretation and history - Mor, Menahem.; Pastor, Jack, 1947-; Stern, Pnina. (Supplements to the Journal for the Study of Judaism, 2011)
An International Josephus Colloquium met in Haifa on 2 - 6 July, 2006. It gathered scholars from Japan, Germany, France, Norway, Italy, Britain, Israel, and the USA who represented different disciplines: bible, history, Judaism, and archaeology. The connecting structure of all the participants was the ancient Jewish historian Flavius Josephus. The fruit of this meeting is presented in twenty four articles and an introduction. Flavius Josephus: Interpretation and History is a multi-disciplinary collection of research on Josephus, the man, the historian, his era, and his writings. It will be of great use to scholars as well as the general public, who take an interest in the literary work of one of the most controversial figures of his era.